Zachowania i preferencje turystyczne uczniów Szkoły Podstawowej im. Kornela Makuszyńskiego w Więcborku = Tourist behavior and preferences of pupils of Kornel Makuszyński Primary School in Więcbork - Zbigniew Podgórski; Agnieszka Mierzejewska; Alicja Ewa Tychoniec (Kazimierz Wielki University, 2015)
Podgórski Zbigniew, Mierzejewska Agnieszka, Tychoniec Alicja. Zachowania i preferencje turystyczne uczniów Szkoły Podstawowej im. Kornela Makuszyńskiego w Więcborku = Tourist behavior and preferences of pupils of Kornel Makuszyński Primary School in Więcbork. Journal of Education, Health and Sport. 2015;5(12):253-261. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35404 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A253-261 http://pbn.nauka.gov.pl/works/681233 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 14.12.2015.   ZACHOWANIA I PREFERENCJE TURYSTYCZNE UCZNIÓW SZKOŁY PODSTAWOWEJ IM. KORNELA MAKUSZYŃSKIEGO W WIĘCBORKU TOURIST BEHAVIOR AND PREFERENCES OF PUPILS OF KORNEL MAKUSZYŃSKI PRIMARY SCHOOL IN WIĘCBORK   Zbigniew Podgórski, Agnieszka Mierzejewska, Alicja Tychoniec IG, WKFZIT, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Abstrakt Celem artykułu jest ukazanie, roli, wpływu turystyki i krajoznawstwa w procesie edukacyjno-wychowawczym dzieci. W artykule podkreślono rolę edukacji regionalnej jako ważnego elementu w procesie kształcenia dzieci i młodzieży. Artykuł prezentuje wyniki badania ankietowego przeprowadzonego wśród uczniów Szkoły Podstawowej im. K. Makuszyńskiego w Więcborku. Badanie miało na celu wskazanie, jaka jest rola i znaczenie turystyki w rozwoju dzieci i jakie preferencje turystyczne mają tak młode osoby.   Słowa kluczowe: preferencje, zachowania, turystyka, krajoznawstwo, czas wolny, rekreacja, edukacja szkolna.   Abstract This article aims to show the impact of tourism and sightseeing in the education and upbringing of children. The article highlights the role of regional education as an important element in the education of children and youth. The article presents the results of a survey conducted among students Kornel Makuszyński Primary School in Więcbork. The survey was designed to identify what the role and importance of tourism in the development of children is and what travel preferences such young people have.   Key words: preferences, behavior, tourism, sightseeing, leisure, recreation, school education.